(untitled) (Sains Humanika, 2022)
The skill of constructing simple sentences is the backbone of Malay writing. Weaknesses in starting writing make it difficult to keep up with learning in the classroom. This study was conducted to improve sentence construction skills among students with learning difficulties. This study is a quantitative study involving respondents who are Special Rehabilitation students’ year 2 in a Pontian district school in the State of Johor who have the potential to be absorbed in the primary class. Self -learning through video using constructivist approach is applied in the teaching and learning of Malay language for this study. A set of pre-test and post-test was conducted to see the level of effectiveness and level of student achievement after using the learning was conducted using Constructivism video. Data were assessed using SPSS with the Wilcoxon Signed Ranked Test. External factors such as interest and inclination also lead to the influence of the effectiveness of test findings. Findings from this study show that, students are very interested in learning to use interactive materials in line with current trends such as video, virtual games and others.